Development of a Measure to Assess Protective Behavioral Strategies for Pregaming among Young Adults. (17th February 2020) - Pedersen, Eric R.; Davis, Jordan P.; Hummer, Justin F.; DiGuiseppi, Graham; Sedano, Angeles; Rodriguez, Anthony; Clapp, John D.
Abstract: Background: Although most young adults drink alcohol, there are specific drinking contexts that are associated with increased risk for alcohol-related consequences. One such drinking context is pregaming, which typically involves heavy drinking in brief periods of time and has consistently been linked to consequences within the pregaming event itself, on a night after pregaming, and in the long-term. Intervention efforts that specifically target this risky behavior are needed, but these efforts need to be informed by empirical work to better understand what behaviors young people engage in that can protect them from pregaming-related harms. Purpose: We designed this study to create a measure of protective behavioral strategies that young people use before, during, and after pregaming to inform future intervention work. Methods: We tested an item pool with 363 young adult college students who engaged in pregaming in the past year and conducted exploratory factor analysis to develop a 19-item Protective Behavioral Strategies for Pregaming (PBSP) scale, which featured four subscales of safety and familiarity, setting drink limits, pacing strategies, and minimizing intoxication. Results: Each subscale negatively and significantly correlated with measures of alcohol use and consequences, though subscales differed in their associations with specific pregaming outcomes and by sex. Conclusion: This initial exploratory examination of the PBSP scale's psychometric properties suggests that use of protective behavioral strategies used specifically during pregaming events may protect young people from heavy drinking and harms. More research with the PBSP scale is encouraged to determine its practical utility as a clinical and assessment tool with young people.